Human Acellular Amniotic Matrix with Previously Seeded Umbilical Cord Mesenchymal Stem Cells Restores Endometrial Function in a Rat Model of Injury - Shan Wang; Cheng Shi; Xiaohui Cai; Yanbin Wang; Xi Chen; Hongjing Han; Huan Shen (Hindawi Limited, 2021)
Background. Abnormal endometrial repair after injury results in the formation of intrauterine adhesions (IUA) and a thin endometrium, which are key causes for implantation failure and infertility. Stem cell transplantation offers a potential alternative for some cases of severe Asherman's syndrome that cannot be treated with surgery or hormonal therapy. Umbilical cord-derived mesenchymal stem cells (UCMSCs) have been reported to repair the damaged endometrium. However, there is no report on the effects of UCMSCs previously seeded on human acellular amniotic matrix (AAM) on endometrial injury. Methods. Absolute ethanol was injected into rat uteri to damage the endometrium. UCMSCs previously seeded on AAM were surgically transplanted. Using a variety of methods, the treatment response was assessed by endometrial thickness, endometrial biomarker expression, endometrial receptivity, cell proliferation, and inflammatory factors. Results. Endometrial thickness was markedly improved after UCMSC-AAM transplantation. The expression of endometrial biomarkers, namely, vimentin, cytokeratin, and integrin β3, in treated rats increased compared with untreated rats. In the UCMSC-AAM group, the VEGF expression decreased, whereas that of MMP9 increased compared with the injury group. Moreover, in the AAM group, the MMP9 expression increased. The expression of proinflammatory factors (IL-2, TNFα, and IFN-γ) in the UCMSC-AAM group decreased compared with the untreated group, whereas the expression of anti-inflammatory factors (IL-4, IL-10) increased significantly. Conclusions. UCMSC transplantation using AAM as the carrier can be applied to treat endometrial injury in rats. The successful preparation of lyophilized AAM provides the possibility of secondary infectious disease screening and amniotic matrix quality detection, followed by retrospective analysis. The UCMSC-AAM complex may promote the better application of UCMSCs on the treatment of injured endometrium.